The Effect Of Profitability, Liquidity, Leverage, Capital Intensity, And Company Size On Tax Avoidance - Sabrina Septiyani Putri; elwisam elwisam; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
The automotive industry is a sector that has a relatively large contribution to the national economy. Where the automotive industry provides an investment value of trillions per year and is able to absorb the work of up to tens of thousands of people. For this reason, the authors conducted this study with the aim of examining the effect of profitability, liquidity, leverage, capital intensity and firm size on tax avoidance in the automotive industry listed on the Indonesia Stock Exchange in 2016 - 2020. In this study, researchers used secondary data with a population of 20 companies. automotive listed on the Indonesia Stock Exchange. Determination of the sample of this study using the purposive sampling method and obtained a sample of 18 automotive companies. The results of this study indicate that the t-test of profitability and leverage variables has a positive effect on tax avoidance, while liquidity, capital intensity and firm size have no effect on tax avoidance. Meanwhile, for the f test of Profitability, Liquidity, Leverage, Capital Intensity, Firm Size has a positive effect on tax avoidance.